2006
DOI: 10.1177/0165551506062325
|View full text |Cite
|
Sign up to set email alerts
|

Data representation factors and dimensions from the quality function deployment (QFD) perspective

Abstract: In order to optimize access to the increasing amount of information, a classic solution has been data representation. The aim of this research is to uncover and systematize the factors and dimensions involved in the data representation issue and more exactly in the planning and design of the information products (IP) and their previous representation processes (RP). QFD (quality function deployment) is a planning tool based on user needs and expectations -quality functions -allowing the planning and design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
5
0
5
Order By: Relevance
“…In general, we identified that there is a difference between the DQ assessment in the financial sector and other sectors. This result confirms that DQ depends on the context of the intended use (Chen and Tseng, 2010;Pinto, 2006). It has been shown that DQ problems increase when there is a large amount of data to be collected and managed (Parssian and Jacob, 2004).…”
Section: Basic Statistic Analysissupporting
confidence: 74%
“…In general, we identified that there is a difference between the DQ assessment in the financial sector and other sectors. This result confirms that DQ depends on the context of the intended use (Chen and Tseng, 2010;Pinto, 2006). It has been shown that DQ problems increase when there is a large amount of data to be collected and managed (Parssian and Jacob, 2004).…”
Section: Basic Statistic Analysissupporting
confidence: 74%
“…In addition, they and their staff spend up to 30 percent % of their working time on checking the quality of data provided [6]. Here, ensuring completeness, correctness and currency of data -such properties are known as data quality dimensions [7] -still remains an important problem for many companies and public institutions [8][9][10][11][12][13]. But how good is an organization's data quality?…”
Section: Introductionmentioning
confidence: 99%
“…Variables and attributes are proposed after a selection process regarding the existing literature (LANCASTER, 2003;HARTLEY et al, 1996;HARTLEY, 2002;HARTLEY et al, 2003;TIBBO, 1992) and our own research on the topic (PINTO, 1995(PINTO, , 2003(PINTO, , 2005. Within the first pragmatic stage two parallel fieldworks are developed around the previously selected sets of abstracting variables and abstract attributes.…”
Section: Methodsmentioning
confidence: 99%